Adab Education in the Online Learning Process - Kamaludin; Ulil Amri Syafri; Akhmad Alim (al-Afkar, Journal For Islamic Studies, 2023)
The Covid-19 pandemic has changed the face of world education, including Indonesia. Education, which was originally carried out face-to-face, now has to be carried out through internet media, commonly known as "Online". This is done in an effort to reduce the spread of the Covid-19 virus. However, this new face of education presents various complex problems for educators, students, and parents of students. In the concept of Islamic Education, the process of adab education is not only in face-to-face learning but also created online. Even though they don't meet face to face, adab in studying science can always be applied in order to give birth to students who have strong character in their morals who are able to realize the development of intellectual amaliyah so that they are efficient for the good of the wider community in their capacity as servants of Allah Subhanahu wa Ta'ala.